Institutional ethnography: a theory of practice for writing studies researchers - LaFrance, Michelle, author; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Reclaims ethnography as a rigorous writing studies research practice, particularly how "work" (a concept defined generously) is co-constituted within writing. The study of work and work processes reveals how institutional discourse, social relations, and norms of professional practice coordinate what people do across time.--Provided by publisher.
Introduction: twenty-first-century exigencies: materialist methods for writing studies researchers -- Institutional ethnography: a theory of practice for writing studies researchers -- How work takes shape: tracing the work of a "shared assignment" in a linked gateway -- The annual review as "boss text" and the coordination of writing center work: uncovering disjunctions between local and national discourse -- Mapping information literacy in a first-year English program: social relations, material conditions, and how things happen -- Conclusion: looking up, studying up, standing up notes.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Research -- Methodology; Academic writing -- Study and teaching (Higher) -- Research -- Methodology; Writing centers -- Sociological aspects; Universities and colleges -- Sociological aspects